Extrapulmonary Tuberculosis is the Leading Presentation among Hospitalized Children: A Single-Center Experience in a Decade - Christine W.S. Basanti; Sonia A. EL Saiedi; Mai M.K. Moawad; Azza K. Abdelmegeid (Cairo University, Faculty of Medicine, Department of Pediatrics, 2021)
Background: With an incidence of twelve tuberculosis (TB) cases for every 100,000 persons in 2019, Egypt is considered a medium-burden country. Nevertheless, guidelines and studies for admission of pediatric TB cases are lacking in developing countries. Aim of the Work: To describe the clinical presentations of hospitalized pediatric TB cases. Materials and Methods: A retrospective analytical study of data collected from the inpatient medical files of children with confirmed TB, from the archives of Giza Chest Hospital (Omraneya), Egypt was implemented during January 2009 to the end of 2018. Results: Of the 76 children hospitalized with TB, 42 were males with a male to female ratio of 1.2:1, 61 (80.3%) patients were from rural areas, and 65 (85.5%) were above six years of age. Extra-pulmonary TB was more common (45 patients; 59.2%) than pulmonary TB (31 patients; 40.8%). Tuberculous LN affection was (N=20) 26.2% of total patients, followed by pleural affection (N=17), then affection of bones (N=4). CNS involvement was among least common presentations (N=4; 5.3%), but was the only type of TB to occur more in preschool children. Moreover, there was an annual rate of change of -2.714 in the recorded numbers of pediatric TB inpatients with no cases in the last two years. Conclusion: Extra-pulmonary TB was more common than pulmonary TB among the hospitalized children. Lymph nodes were the most common extra-pulmonary site of affection. School-aged children were a majority as well as rural residents. These findings warrant evoking awareness among physicians about the various presentations of pediatric TB.